Fibro-adipogenic progenitor cells from murine SMA muscles are intrinsically adipogenic - Yangyi E. Luo; Zoe Abe-Teh; Tarek Alsaghir; Katie D. Heiden; Kari B. Basso; Elisabeth R. Barton (Proceedings of the National Academy of Sciences, 2026)
Spinal muscular atrophy (SMA) is a neurodegenerative disorder caused by mutations in the SMN1 gene. Although classically viewed as a neurogenic disease, SMA patients exhibit poor skeletal muscle regeneration and increased fatty-fibrotic infiltration. Fibro-adipogenic progenitors (FAPs) are mesenchymal precursor cells that contribute to muscle remodeling and underlie fat and fibrosis formation. Because FAPs transiently express Smn1 during regeneration, FAPs were examined in muscles from adult C/C SMA and control mice to determine if reduced Smn activity altered their properties. We performed a nonbiased screen of FAPs following BaCl 2 -induced injury using an in situ cell surface proteomic strategy that probed the cellular membrane and environment of FAPs in early regeneration. Proteomic profiling revealed early adipogenic priming in SMA tissues, with increased levels of perilipin-4 and adipocyte lipid-binding proteins. Significantly more adipocytes accumulated in C/C SMA muscles after glycerol injection versus controls. Further, SMA FAPs produced more fat than control FAPs when transplanted into glycerol injured muscles lacking FAPs. RNA sequencing of FAPs isolated after BaCl 2 or glycerol injury identified transcriptional enrichment of lipid biosynthesis and dysregulated lipid metabolism in SMA FAPs. Primary FAPs isolated from C/C SMA muscles mirrored heightened adipocyte formation, which was normalized by increasing Smn activity with Risdiplam. Conversely, adipogenesis of primary FAPs from control muscles was enhanced when subjected to siRNA Smn1 knockdown. Together, these findings demonstrate that reduced Smn activity potentiates intrinsic adipogenic bias in FAPs that may contribute to pathological fat deposition in SMA muscle.